Impact of pharmacist-interpreted pt-qPCR technology on antimicrobial use and clinical outcomes in patients with lower respiratory tract infections: a retrospective cohort study - Wang, Ziyi; Wang, Jing; Liu, Yan; Wei, Yuanyuan; Zhao, Yan; Yuan, Shizhao; Liu, Shuai; Yin, Wanyi; Yu, Jing (Frontiers in Pharmacology, 2025)
ObjectiveLower respiratory tract infections (LRTIs) are a leading cause of morbidity and mortality worldwide and contribute to excessive empirical antibiotic use due to diagnostic delays. Rapid and accurate pathogen identification is essential for guiding targeted antimicrobial therapy and improving drug outcomes.AimThis study aimed to evaluate the impact of pathogen-targeted quick multiplex PCR (pt-qPCR) compared to conventional microbiological testing on antimicrobial use and clinical outcomes in hospitalized patients with LRTIs.MethodsIn this retrospective cohort study conducted at a tertiary hospital in China (March 2023–March 2024), patients with LRTIs were assigned to either a conventional testing group or a pt-qPCR group. Outcomes included pathogen detection rate, length of hospital stay (LOS), antimicrobial days of therapy (DOT), antimicrobial duration before and after testing, time to targeted therapy, mortality, and ICU transfer rate.ResultsA total of 220 patients were enrolled (conventional: n = 112; pt-qPCR: n = 108). Baseline characteristics were comparable, except for higher chronic pulmonary disease prevalence (58.0% vs. 20.4%, P < 0.001) and lower IL-6 levels (133.22 vs. 171.28, P < 0.001) in the pt-qPCR group. Pathogen detection was significantly higher with pt-qPCR (94.4% vs. 53.6%, P < 0.001). Compared to conventional testing, the pt-qPCR group showed reduced LOS (16 vs. 16 days, P = 0.041), DOT (20 vs. 24 days, P = 0.013), post-test antimicrobial use (8 vs. 12 days, P < 0.001), and ICU transfer rate (31.5% vs. 49.2%, P = 0.006). Mortality did not differ significantly between groups. The pt-qPCR group had a higher rate of antimicrobial regimen adjustment (34.3% vs. 19.6%, P = 0.014) and fewer instances of escalation. A broader pathogen spectrum was detected using pt-qPCR, including 208 bacteria, 73 fungi, and 103 viruses, with 87 patients harboring multiple pathogens.ConclusionPharmacist-interpreted pt-qPCR significantly improves pathogen detection and optimizes antimicrobial therapy in LRTI patients. Its clinical use may enhance antibiotic stewardship, reduce ICU burden, and support precision medicine in respiratory infections.